Combined detection of CEA and CA125 for the diagnosis for lung cancer: A meta-analysis - Wu, Li-xin; Li, Xiao-feng; Chen, Hua-fei; Zhu, You-cai; Wang, Wen-xian; Xu, Chun-wei; Xie, Dong-fang; Wan, Yang; Du, Kai-qi (Cellular and Molecular Biology, 2018)
This study aimed to systematically evaluate the value of combined detection of serum CEA and CA125 concentrations for the diagnosis of lung cancer. Related studies regarding the diagnosis of lung cancer were searched in PubMed, Embase, CNKI, and Wanfang using a computer. The number of patients who were true-positive, false-positive, false-negative, and true-negative were extracted from each study. Meta-analysis was performed using the Meta-Disc l.4, RevMan 5.3. Seven studies involving 2,216 cases were finally included. Regarding the diagnosis of lung cancer, the sensitivity, specificity, and diagnostic odds ratio of combined CEA and CA125 detection were higher than those of CEA detection alone. The area under the curve (AUC) of combined detection was 0.90, whereas the independently detected AUC was 0.73. Combined CEA and CA125 detection has higher diagnostic efficiency for lung cancer than CEA detection alone. The significance of combined serum CEA and CA125 detection in lung cancer is confirmed.